Anesthetic Management of a Patient with a Giant Pericardial Cyst Compressing the Right Atrium - Mohammad Hadi Gharedaghi; Saman Ahmadi; Arjang Khorasani; Farzad Ebrahimi (Case Reports in Anesthesiology)
Pericardial cysts are rare mediastinal cysts composed of a single fluid-filled mesothelial layer and can be congenital in origin or develop secondary to pericarditis, trauma, or infection. Although most pericardial cysts are asymptomatic, life-threatening complications can occasionally occur. We report on a 57-year-old man with an asymptomatic 9 cm pericardial cyst that was incidentally found as an abnormal cardiac silhouette on routine chest radiography. Further imaging confirmed the presence of a pericardial cyst that was compressing the right atrium. The patient underwent successful video-assisted thoracoscopic removal of the pericardial cyst under general anesthesia. The patient’s postoperative course was uneventful and he was discharged on postoperative day 1 in a stable condition. To our knowledge, this is the first report regarding the anesthetic management of a patient with a giant pericardial cyst undergoing thoracic surgery. Knowledge regarding the perioperative challenges associated with the removal of pericardial cysts can prevent complications and improve patient outcomes.